Conductivity or resistivity measurement of a conductive media - Yang, Li Feng (2009)
My project objective is to measure the conductivity or resistivity of a conductive medium. What I chose is the grounding resistivity measurement. Grounding of power systems is achieved by embedding metallic structures (conductors) into earth and electrically connecting these conductors to the neutral of the power system. In my project I firstly developed some basic equations for calculating the resistance of ground rods followed by discussing Four-Electrode method and Fall-of-Potential method which are used to calculate the resistivity of saline water and the resistance of ground rod respectively. Finally, I used MAXWELL 2D simulator to find the models to calculate the resistivity of saline water.